Benefits of Moringa oleifera for human and animal health: Literature review (Research, Society and Development, 2021)
Moringa oleifera Lam. It is a species belonging to the Moringaceae family, arboreal, cultivated all over the world, for presenting several applications, from human and animal health to use for environmental purposes, such as water purification. From the leaves, the roots of the plant have a high medicinal value and several studies have proven their therapeutic effects, such as powerful anti-inflammatory, glucose reduction, anti-cholesterol, hepatoprotective, anti-cancer and antimicrobial properties. The purpose of this review article is to present the various benefits of Moringa oleifera in human and animal health. Therefore, an integrative review was carried out in this article, and a total of 63 scientific articles were studied, in English, Spanish and Portuguese. Based on the studies reviewed, it was confirmed that several parts of the plant have therapeutic effects, such as leaves, seeds, flowers and roots have phytochemicals, such as flavonoids, phenols, alkaloids, tannins, saponins, glucosinalates, phytates, oxalates, proteins and vitamins, responsible for their therapeutic action, and their effectiveness in responding to treatments, depends on the forms of presentation and the dose administered.